Nephron Sparing Surgery for Renal Angiomyolipoma with Inferior Vena Cava Thrombus in Tuberous Sclerosis. (23rd February 2014) - Riviere, Adrien; Bessede, Thomas; Patard, Jean-Jacques
Abstract : Introduction . Angiomyolipoma is a common benign renal tumor. It is associated with Tuberous Sclerosis Complex (TSC) in 20% of patients. Angiomyolipomas are classically multiple, bilateral, and growing; they may lead to complications such as Wunderlich syndrome or, in rare cases, to venous extension. Observation . a 74-year-old woman with TSC presented with an angiomyolipoma of the right kidney with inferior vena cava (IVC) fatty thrombus. She underwent partial nephrectomy and thrombectomy. After a 7-year follow-up there was no evidence of recurrence or metastasis and her renal function was preserved. Review of Literature . It is the 44th reported angiomyolipoma associated with IVC thrombus. The mean size of angiomyolipomas was 86.1 mm and 67.4% of patients were symptomatic. Pulmonary embolism was found in 6 patients. There were 2 cases of recurrence/metastatic outcome after radical nephrectomy and thrombectomy. They were associated with epithelioid form. The mean size of epithelioid tumors was significantly bigger than in classical angiomyolipomas (127.1 mm versus 82.6 mm, P = 0.037 ). With a median follow-up of 12 months, 91.3% of patients were recurrence and metastasis free, with 3 cases of nephron sparing surgery. Conclusion . Nephron sparing surgery for angiomyolipoma with IVC fatty thrombus can be safely performed in TSC, even in sporadic angiomyolipoma.